Works Well with Others: Gendered Mediation of Collaborative Leadership Skills. (3rd April 2022) - Trimble, Linda; Curtin, Jennifer; Auer, Meagan; Wagner, Angelia; Woodman, V. K. G.
ABSTRACT: This research note reports an intriguing finding, reached inductively from textual analysis of newspaper coverage of the leadership attributes of 22 women and men premiers in Australia and Canada. When introducing these newly selected subnational government leaders to the public, journalists articulated their capacity to work well with others as an important leadership competency. Women and men premiers alike were described as inclusive, conciliatory, and consultative, and these qualities were highlighted as integral to effective decision-making and sound governance practices. Our research challenges a central proposition of the gendered mediation thesis: that news coverage of political leaders foregrounds and lauds the agentic qualities traditionally associated with men and masculinity while downplaying and denigrating communal qualities linked to women and femininity. Evidence of media attention to and praise for collaborative leadership traits indicates a feminization of politics that disrupts gender stereotypes in a manner helpful to women's political ambition.